Chapter 5 Urban Migrant and Refugee Solidarity - Bauder, Harald (Taylor & Francis, 2022)
Urban and local communities around the world are practising migrant and refugee solidarity. This chapter first identifies several dimensions that define a common urban solidary approach: legal, discursive, identity-formative, and scalar dimensions. Second, the chapter examines cities around the world where these dimensions can be observed although various labels are used to describe urban solidarity approaches. In Canada, the USA, and the UK, the label "sanctuary city" is often used; in Spain, Barcelona calls itself a "city of refuge," and municipalities in Chile refer to themselves as "commune of reception" or "inclusive community." Dimensions of urban solidarity approaches can also be observed in parts of Africa and Asia. By focussing on different continents and diverse geopolitical contexts, the chapter illustrates the complexity in the way in which urban migrant and refugee solidarity is understood and practiced.